Faktor-Faktor Yang Memengaruhi Minat Wajib Pajak Orang Pribadi Dalam Penggunaan E-Filing Pada Kpp Pratama Serang - Andi Andi; Dara Novita Sari (Sains: Jurnal Manajemen dan Bisnis, 2017)
This research aimed to investigate the factors that influenced perceived usefulness, perceived satisfaction, perceived ease, perceived the security and privacy, readiness technology taxpayers information ,to use toward the intention taxpayers in using e-filing in KPP Pratama Serang. This research used primary data obtained from questionnaires. The sample used were the taxpayer registered in the Tax Office Serang that using e-filing. The sampling technique used was purposive sampling. Of the 150 questionnaires distributed, the number of questionnaires returned was 130 questionnaires. The analytical method used is the analysis of Structural Equation Modeling (SEM). The data were processed using software Smart Partial Least Square (SmartPLS) version 3.The results of this study revealed that all the independent variables in this study, perceived usefulness, perceived satisfaction, perceived ease, perceived security and privacy, readiness technology taxpayers information significant effect on the interest of individual taxpayers in the use of e-filing.